By the light of the moon - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2002)
Someone menacing is after itinerant artist Dylan, his autistic brother, and their new traveling companion, Jilly, a stand-up comic who has visions. And they only have the novel's 24-hour time span to figure out who it is.
Keywords: Artists -- Fiction; Psychics -- Fiction; Brothers -- Fiction; Women comedians -- Fiction; Autism -- Patients -- Fiction; Suspense fiction